The Role of Britain in Making Baghdad Alliance and Its impact on the Kurdish Issue in Iraq: (1955-1958) - Ali, Hameed Hussein; Al-Hiti, Ghassan Mouteb Abdul Karem (Al-Adab Journal, 2020)
Many important developments emerged on the international policy after the end of the World War II on 1945 represented by the appearance of the conflict among the triumphant countries obviously. These countries were divided into two fronts: the socialist one led by the Soviet Union and the eastern European countries and the Capitalist front led by the United States, Britain and the western European countries. Thus, the United States and Britain intended to form a strong front in the Middle East against the Soviet Union especially after the increase of the communist danger on the west and its regimes. Since the countries divide Kurdistan (Iraq, Iran, Turkey and Syria), they represent the more important part in the zone, so the United States moves toward them to achieve success of its projects to restrict the Soviet Union and its alliance. The countries which divide Kurdistan realized that any alliance in which the greater countries take part is a good opportunity to unify their attitude and get rid of their discords to stand against the greater danger; the Kurdish issue. Despite the discords which characterize its relations, it does not hesitate to enter any alliance which ensures the restriction of the Kurdish national movement and suppress it. The importance of the present topic lies in its shedding light on the activity of the colonial alliance which observes the Kurdish national movement in the countries which are still dividing Kurdistan, despite getting all documents which are concerned with this topic, the researcher keeps no effort in writing this invaluable research in its present form.